All Days 2005
DOI: 10.2118/97299-ms
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Screen Failures in Unconsolidated, High-Permeability Sandstone Reservoirs: Reversing the Trend

Abstract: Horizontal screen failures can be serious, resulting in expensive remedial operations including early abandonment, in the extreme case. Globally, screen failures in horizontal wells completed in loose unconsolidated sandstone reservoirs have become common. Consequently, from completion and longevity perspectives, a high percentage of horizontal wells have not achieved the desired result: sand-free, high sustained-productivity producers. Individual companies have performed studies in this dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Many authors have examined causes and failure modes of SAS. Most of these studies concluded that screen erosion is by far the most common failure mechanism [ [58] , [59] , [60] ]. Screen erosion is due to the mechanical wear of the retention media, weave or wire.…”
Section: Sand Screen Integrity and Failurementioning
confidence: 99%
“…Many authors have examined causes and failure modes of SAS. Most of these studies concluded that screen erosion is by far the most common failure mechanism [ [58] , [59] , [60] ]. Screen erosion is due to the mechanical wear of the retention media, weave or wire.…”
Section: Sand Screen Integrity and Failurementioning
confidence: 99%
“…Biostabilization has lately emerged as a sustainable option capable of overcoming some of the limits of traditional soil improvement techniques (Umar et al, 2016;Rahman et al, 2020;Xue et al, 2023). Efforts are being made in soil stabilization by adapting bacteria to enhance soil performance (Banik et al, 2023;Sharma and Satyam, 2023). Enzyme-induced calcite precipitation (EICP) is a promising approach due to its simplicity of application in the field and compatibility across various types of soil (Saif et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to chemical methods, mechanical techniques are typically more expensive and time-consuming ( ben Mahmud et al, 2020 ). They also face other issues like a decline in productivity index, complicated installation equipment, installation-related damage, workover difficulties, zonal isolation issues, collapsed screens, and equipment erosion and plugging ( Arukhe et al, 2005 ; Abduljabbar et al, 2022 ). Additionally, they are useless at containing tiny sand particles.…”
Section: Introductionmentioning
confidence: 99%